2022
DOI: 10.1186/s10033-021-00675-z
|View full text |Cite
|
Sign up to set email alerts
|

Tire Road Friction Coefficient Estimation: Review and Research Perspectives

Abstract: Many surveys on vehicle traffic safety have shown that the tire road friction coefficient (TRFC) is correlated with the probability of an accident. The probability of road accidents increases sharply on slippery road surfaces. Therefore, accurate knowledge of TRFC contributes to the optimization of driver maneuvers for further improving the safety of intelligent vehicles. A large number of researchers have employed different tools and proposed different algorithms to obtain TRFC. This work investigates these d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(21 citation statements)
references
References 118 publications
0
21
0
Order By: Relevance
“…These estimations are then used to calculate the longitudinal slip on each wheel and for the model used by the controller. To simplify the algorithm, the TRFC is supposed to be obtained by some estimation method [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ] and the optimal tire slip that maximizes the braking force is calculated by means of the Burckhardt friction model. Finally, the controller generates the necessary braking pressure for each wheel in order to minimize the error between the optimal and current longitudinal slip.…”
Section: Problem Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…These estimations are then used to calculate the longitudinal slip on each wheel and for the model used by the controller. To simplify the algorithm, the TRFC is supposed to be obtained by some estimation method [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ] and the optimal tire slip that maximizes the braking force is calculated by means of the Burckhardt friction model. Finally, the controller generates the necessary braking pressure for each wheel in order to minimize the error between the optimal and current longitudinal slip.…”
Section: Problem Formulationmentioning
confidence: 99%
“… Scheme of the control architecture implemented in Simulink and CarSim [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…It often happens that the wheels are one of the first elements transmitting destructive forces-during collisions and road accidents. Many studies on vehicle traffic safety have shown that the tire road friction coefficient (TRFC) is correlated with the accident probability [1][2][3][4]. According to the report on road safety in Poland [5], in 2020 the share of road accidents due to technical reasons was 17.1%.…”
Section: Introductionmentioning
confidence: 99%
“…Establishing the relationship between the mileage and the technical condition of car tires is a significant problem of road safety. Along with the wear of the tires, the so-called drainage volume of the tread, which is directly related to its tread height [1,5,6] and [7,11,20] as in the works [17,19] is reduced. Of particular importance is the effect of various parameters on the vehicle's braking distance.…”
Section: Introductionmentioning
confidence: 99%